2021
DOI: 10.17113/ftb.59.04.21.7204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chia Seed, Buckwheat and Chestnut Flour Addition on the Overall Quality and Shelf Life of the Gluten-Free Biscuits

Abstract: Research background. In spite of being a significantly growing segment, there still exist problems regarding the nutritional, technological and sensory profiles of gluten-free products. Thus, the combination of a variety of functional ingredients is required in order to achieve the desired product quality. Experimental approach. Flours of chestnut, buckwheat and potato were chosen in this study because they are all gluten-free; nutritionally richer and technologically more advantageous compared to whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In particular, the latter authors reported that a substitution with 500 g/kg of chestnut flour might represent the best compromise between quality and storage stability. Also, Torra et al (2021) [90] and Silav-Tuzlu and Tacer-Caba (2021) [91] tested the addition of chestnut flour in the production of gluten-free biscuits with similar results. According to Torra et al (2021) [90], the addition of chestnut flour to the biscuit formulation increased the values of G' and G" but reduced the loss factor compared with the doughs made using chickpea flour.…”
Section: Innovative Applications Of Chestnut Flour In the Food Industrymentioning
confidence: 87%
“…In particular, the latter authors reported that a substitution with 500 g/kg of chestnut flour might represent the best compromise between quality and storage stability. Also, Torra et al (2021) [90] and Silav-Tuzlu and Tacer-Caba (2021) [91] tested the addition of chestnut flour in the production of gluten-free biscuits with similar results. According to Torra et al (2021) [90], the addition of chestnut flour to the biscuit formulation increased the values of G' and G" but reduced the loss factor compared with the doughs made using chickpea flour.…”
Section: Innovative Applications Of Chestnut Flour In the Food Industrymentioning
confidence: 87%
“…During the last decade, the request to gluten free product has increased (Shevkani et al ., 2022). Silav‐Tuzlu & Tacer‐Caba (2021) investigated the using of chia seeds in gluten free biscuits and reported that chia seeds caused an increase in the overall acceptability and flavour scores of biscuits. Laczkowski et al .…”
Section: Resultsmentioning
confidence: 99%
“…The eccentricity was calculated as the ratio between d 1 and d 2 . Spread factor was calculated as the ratio between the average diameter and average thickness ( 3 ). Sample puffiness (SP) was calculated as shown in the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…For the new food ingredients, especially in the case of gluten-free products, it is desirable to provide dual benefit of enhancing nutritional and retaining or improving technological quality of final products. How gluten-free products are recognized as products with inferior nutritional quality, many studies with different technological and compositional approaches were devoted to the fortification of this category of food (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%